Odpowiedzi

2009-11-13T22:33:03+01:00
W (x)= x - ax³ + bx² - (2a + b)× x +5 oraz W (1) =0 i W(-1)=24

W(1)=1-1*a+1*b-2a-b+5=0
-a+b-2a-b+5=0
-3a=-5/:(-3)
a =5/3
W(-1)=24
W(-1)=-1+a+b+2a+b+5=24
3a+2b+4=24
3a+2b=20
wstawiamy wartość a
3*5/3+2b=20

5+2b=20
2b=15/:2
b=15/2

Zatem
W(x)=x-5/3x³+15/2x²-(10/3+15/2)x+5=x-5/3x³+15/2x²-50/6x+5
Najlepsza Odpowiedź!
2009-11-13T22:33:39+01:00
Oblicz a oraz b, wiedząc, że:
W (x)= x - ax³ + bx² - (2a + b)× x +5 oraz W (1) =0 i W(-1)=24
W (1)= 1 - a1³ + b1² - (2a + b)× 1 +5=0
W (-1)= -1 - a(-1)³ + b(-1)² - (2a + b)(-1) +5=24

1 - a + b - 2a- b +5=0
-1 + a + b+ 2a + b +5=24

- 3a=-6
2b=20-3a

a=2
2b=20-3*2

a=2
b=7
2009-11-13T22:35:50+01:00
W(x)=x⁴-ax³+bx²-(2a+b)x +5
W(1)=1-a+b-2a-b+5=0
W(-1)=1+a+b+2a+b+5=24

-3a=-6
3a+2b=18

a=2
2b=18-3a
2b=18-6
b=6

a=2
b=6